Practical differences in business valuation using the market value, value in use and the value for price negotiations - Vlček, Michal (2012)
This thesis aims to explain the basic characteristics of valuation method in practice use. The first chapter is about basic character of each method of valuation and factors which influence its applicability. The second chapter mentions estimation of market value/appraisal, includes affecting factors. Then, the third and fourth parts aim to comparing these appraisals (market. vs. price bargaining, subjective and objective, complex appraisal) and price formation for price bargaining in the Czech a EU market. Chain of model facets in appraisal is demonstrated by fair example in the fifth part. Mainly prefeasibility appraisal and bargaining based on the categories of value are followed. These entire complexes comparing of advantages and disadvantages of each category of value with a focus on valuation methods, in particular the consequences of their use are gone to conclusion of my thesis. At the very end of the thesis there are the main points of practical differences and their benefits to it and their contributions summarized.